Factors that influence the landscape recovery of the sector of the ancient alameda of the Bolognesi avenue - Tacna. 2018 - Santos Duarte, Juan Carlos (2019)
The present investigation is aimed at determining the main landscape factors that influence the recovery of the Alameda Antigua sector. Avenue Bolognesi, Tacna-2018. The research centered its methodology, under a quantitative approach, basic type, non - experimental design of contrast level explanatory, this level is assumed because it establishes cause and effect between the variables: Main factors of recovery and recovery landscape. The questionnaire was applied as a measuring instrument; which allowed to collect information, relate and measure the variables of study, make correlations and comparisons. The sample consisted of 218 architects. The main factors that influence the recovery of the Alameda Antigua sector  of Avenida Bolognesi, Tacna-2018, are environmental conflicts and potentialities, social value and management mechanisms.